Accuracy in agricultural citizen science: farmers’ assessment of harvest output in Ghana - Ulzen, Jacob; van Etten, Jacob; Dorado Betancourt, Hugo Andres; Osei Bonsu, Nana Oduro; Bush, George (2024)
This study aims to assess methods for farmer-led yield estimation in decentralized on-farm trials, addressing whether farmers can accurately collect data. Key research questions involve evaluating yield estimation techniques and farmer accuracy without extensive training.